Informal interference in the judiciary in new democracies: a comparison of six African and Latin American cases. Issue 7 (9th November 2016) - Llanos, Mariana; Tibi Weber, Cordula; Heyl, Charlotte; Stroh, Alexander
ABSTRACT: This article focuses on the efforts of power holders – at the executive or the legislative level – to influence or curb court activity informally or extra-legally, an acknowledged but under-researched topic in studies of judicial politics. We first define informal judicial interference and operationalize the concept; we then explain how we collected information on the topic through systematic cross-country interviewing. Our concept focuses on judicial intervention actions exercised by political actors once judges are on the bench. We distinguish these actions according to type – direct or subtle – and further differentiate each type according to six different modes. We provide new empirical data on informal interference in six third-wave democracies, three in Africa (Benin, Madagascar, and Senegal) and three in Latin America (Argentina, Chile, and Paraguay). Our empirical findings, first, confirm the importance of informal practices in shaping political-judicial relations. Second, they point to long-standing legacies and to the level of socio-economic development as possible explanations for different performances in terms of the prevalence and severity of informal interference in the judiciary in these newly established democratic regimes